The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1039/c5lc00945f
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidic cell-phoresis enabling high-throughput analysis of red blood cell deformability and biophysical screening of antimalarial drugs

Abstract: Changes in red blood cell (RBC) deformability are associated with the pathology of many diseases and could potentially be used to evaluate disease status and treatment efficacy. We developed a simple, sensitive, and multiplexed RBC deformability assay based on the spatial dispersion of single cells in structured microchannels. This mechanism is analogous to gel electrophoresis, but instead of transporting molecules through nano-structured material to measure their length, RBCs are transported through micro-str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 61 publications
(83 reference statements)
0
21
0
Order By: Relevance
“…Traditional single cell manipulation, including micropipette aspiration 33,34 , optical tweezers 35 , and atomic force microscopy 36 , involve technically challenging experiments that require skilled personnel and highly specialized equipment. Microfluidic approaches for deformation based RBC deformability analysis include the measurement of capillary obstruction 37 , wedging in tapered constrictions 38,39 , transiting time through constrictions [40][41][42][43] , and transiting pressure through constrictions 17,44,45 . While these approaches greatly simplified RBC deformability analysis, the throughput of these processes are still relatively limited.…”
Section: Introductionmentioning
confidence: 99%
“…Traditional single cell manipulation, including micropipette aspiration 33,34 , optical tweezers 35 , and atomic force microscopy 36 , involve technically challenging experiments that require skilled personnel and highly specialized equipment. Microfluidic approaches for deformation based RBC deformability analysis include the measurement of capillary obstruction 37 , wedging in tapered constrictions 38,39 , transiting time through constrictions [40][41][42][43] , and transiting pressure through constrictions 17,44,45 . While these approaches greatly simplified RBC deformability analysis, the throughput of these processes are still relatively limited.…”
Section: Introductionmentioning
confidence: 99%
“…However, both methods are time and labor intensive (tens of cells per hour), posing challenges for examining large populations of cells to either obtain statistically valid conclusions or identify rare sub-populations. Recent advances in micro-/nano-fabrication technologies have opened up a range of new mechanophenotyping technologies that can measure deformations of tens to hundreds of cells per second [11][12][13][14][15][16][17][18][19] . We recently reported a technology, called deformability cytometry, in which a cross-slot microfluidic channel is employed to generate a hydrodynamic extension zone where individual cells are exposed to uniform hydrodynamic stress and deformed 20 .…”
Section: Introductionmentioning
confidence: 99%
“…4(d)). 61 Based on application of di®erent micro°uidic channels, they all suggested that erythrocyte deformability decreased signi¯cantly under various abnormal conditions, such as malaria-infection, 62,63 blood storage lesion, 64,65 diabetes 66,67 and sickle cell disease. 68,69 Compared with the optical tweezers and the micropipette aspiration, the micro°uidic channels provided a unique opportunity to investigate erythrocyte deformability in a rapid, highthroughput and relatively easy-to-use method at single-cell level.…”
Section: Micro°uidic Channelsmentioning
confidence: 99%